Analysis of the 2022 president's budget - Charlotte Justine D. Sicat; Robert Hector G. Palomar (Philippine Institute for Development Studies (PIDS), 2021)
With the country still managing the COVID-19 pandemic, the election of national and local officials next year, and an increase in resources available to local governments units (LGUs) with the implementation of the Supreme Court ruling on the Mandanas-Garcia petition, major shifts in Philippine governance can be expected in 2022. Increased resources for LGUs reduce the fiscal space for national government efforts to jumpstart the economy from the pandemic-induced slump. How then does the President's budget for 2022 plan to address the many urgent needs, such as providing social safety nets to minimize economic and human capital scarring and sustaining strategic infrastructure investments to spur economic growth? This study provides an overall perspective of the budget and examines how the 2022 National Expenditure Program (NEP), also called the President's budget, embodies the priorities identified by the national government. In terms of the continued COVID-19 management and human capital investment and consistent with declared priorities in the National Budget Call, spending on health and social protection is prioritized. With the implementation of the Supreme Court ruling, the national tax allotment (formerly known as the internal revenue allotment) is 38 percent higher in 2022, almost 20 percent of the proposed budget. Despite greater devolution, the budget still includes some LGU assistance programs, such as the new growth equity fund (GEF) targeted at poorer LGUs. Institutional reforms, such as the Medium-Term Information and Communications Technology Harmonization Initiative (MITHI) and convergence programs, are also present to help reshape and improve the delivery of public goods and services through investments in information and communications technology. However, the 2022 NEP is projected to increase the debt-to-GDP ratio to 60.8 percent, the highest since 2006. To benefit from increased borrowing, fiscal authorities need to be both strategic and prudent in spending.
Keywords: 330; COVID-19 pandemic; Expansionary fiscal policy; Mandanas ruling; Recoveras one